Frequency Refarming Analysis For Lte Implemetation In Indonesia Using Seamcat Simulation - Raden Arjani Rosalina; Rendy Munadi; Arfianto Fahmi (eProceedings of Engineering, 2015)
Abstract— The LTE technology is expected to offer a number of distinct advantages over other wireless technologies. Scarcity of spectrum had been encourage regulator and provider to refarmed the spectrum. Spectrum refarming for LTE in 900MHz, 1800 MHz or 2100 MHz frequencies band is considered to be triggered the potential degradation of existing services such as GSM and UMTS. The simulation’s results decribe that in those frequencies band options, LTE can well coexist with other technologies in the ecosystem such as GSM and UMTS. Overall simulation’s results show that at 1800 MHz while LTE is interfered by LTE and others such as GSM and UMTS, the performance is lower than other frequencies, so the best option is at 900 MHz or 2100 MHz of the frequencies. Index Terms—Refarning, Coexistence, Throughput, SINR, Performance